Inovasi Motif Patchwork pada Kemeja Pria dengan Sumber Ide Blue Jay - Kholifah Tasyakuranti, Mauliddina; Suhartini, Ratna (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
In this research, the aim of the author is to find out the results of developing the Blue Jay idea source patchwork motif on men’s shirts, apart from that, to find out the finished product of the shirt by applying the Blue Jay idea source patchwork motif. The research method used in this research is the double diamond model, where this method has 4 research stages including: discover to carry out research through patchwork motifs, define to carry out research through sources of ideas as inspiration for men’s shirts, develop to carry out shirt design development, and stage Lastly, namely deliver, the best design will be selected to be realized. The instrument or data collection tool uses a questionnaire containing a number of questions that must be answered or responded to by the respondent. The instrument used in this research is design selection through a questionnaire for Innovation in Patchwork Motifs on Men’s Shirts with the Idea Source Blue Jay. Observation of the finished shirt results was also carried out through a questionnaire which was assessed by 50 male respondents aged 18-26 years. The analysis technique used is descriptive with the presentation of average or mean data. The finished result is the development of an innovative design for Patchwork Motifs on Men’s Shirts with the Bluejay Idea Source in accordance with the moodboard. The finished result of Patchwork Motif Innovation on Men’s Shirts with the Bluejay Idea Source is in the very good category. The patchwork motif development design only uses rectangular and triangular geometric shapes so there is still a lack of design development.